An investigation into the synergistic strengthening mechanism of ionic liquid and nanoparticles as a hybrid nanofluid in friction interface. (January 2022) - Peng, Ruitao; He, Xiangbo; Tang, Xinzi; Tong, Jiawei; Zhao, Linfeng; Peng, Xing
Abstract: In this current study, the multi-walled carbon nanotubes (MWCNTs) were non-covalently modified with 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMIm]BF4 ) and a water-based hybrid nanofluid was prepared. Suspension stability and tribological tests were carried out for this study. Furthermore, the changes of anti-wear and anti-friction properties under various mass ratios of molybdenum disulfide (MoS2 ) and MWCNTs were emphatically explored. It revealed that when compared with deionized water and mono-nanofluid, the synergistic strengthening effect between nanoparticles and ionic liquid (IL) results in excellent anti-wear and anti-friction performance of the IL-MWCNTs/MoS2 hybrid nanofluid, and while the optimal anti-wear and anti-friction performance was achieved when the mass ratio of MWCNTs and MoS2 is 2:1. Highlights: The suspension stability of IL-MWCNTs/MoS2 hybrid nanofluid was studied. The most suitable dispersant for IL-MWCNTs/MoS2 hybrid nanofluid was sifted. The anti-wear and anti-friction mechanism of IL-MWCNTs/MoS2 hybrid nanofluid was studied. The optimal tribological property was achieved when the mass ratio of MWCNTs and MoS2 at 2:1.